Estudio comparativo de tres cultivares de mandarina sobre dos patrones - Bello, L.=700 1 Nuñez, M.
(Es, En)
Ilus., 8 ref.
Keywords: CITRUS RETICULATA; INJERTO; CITRUS AURANTIUM; ALTURA; PRODUCCION; CALIDAD; FRUTAS; CUBA; NARANJO AGRIO